The Effect Of Job Stress And Work Environment On Tax Auditor Performance: Motivation As A Variable Of Mediation - Wijaya, Welly Saputra; Ratnawati, Vince; Andreas, Andreas (Program Pascasarjana, Universitas Riau, 2021)
This study has several objectives, first to analyze the effect of job stress, work environment and motivation on the performance of tax auditors. Second, analyze the effect of job stress, work environment on the motivation. Third, to analyze the effect of job stress and work environment on the performance of tax auditors after being mediated by motivation. Motivation is expected to have an influence on the performance of tax auditors. The population of this research are 166 tax auditors in the Riau General Directorate Regional Office environment as many as 153 people and the sampling method is saturated samples. Data processed is primary data obtained by processing questionnaire data and were analyzed with the help of the Smart PLS Version 3.2.8 program. The results of the study prove that job stress does not affect the performance of the tax auditors. Work environment and motivation positively and significantly affect the performance of tax auditors. Job stress and work environment significantly affect the motivation. The last, that motivation does mediate the relationship between job stress and work environment to the performance of tax auditors.